Immersion in the bureaucratic field: Methodological pathways. (June 2019) - Hahonou, Eric Komlavi; Martin, Tomas Max
Abstract: The introduction argues that while the legitimacy of bureaucracy as an object of inquiry is well established, little is generally said on the methodologies mobilized by ethnographers to study the bureaucratic field. The special issue is a contribution to fill this gap. The authors characterize bureaucracy as a mode of control by way of four dimensions—service, rule, violence, and secrecy—and propose three methodological pathways through which ethnographers may immerse in the bureaucratic field. The first pathway, "stages, " is concerned with the methodological reflections on accessing the bureaucratic stage and of being led in by bureaucrats as they perform their stage work. The second focuses on "techniques" and considers the implications of immersing oneself in a distinct technical landscape. The third pathway concerns the ethnographer's positionality, drawing attention to the deep reflexivity and unstable ethics of bureaucracy ethnography. The authors invite bureaucracy ethnographers to pursue these pathways and to engage in a critical reflection on their fieldwork practices.